2020
DOI: 10.1002/hon.2820
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world efficacy and safety analysis of combined carfilzomib, lenalidomide, and dexamethasone (KRd) in relapsed/refractory multiple myeloma

Abstract: Carfilzomib–lenalidomide–dexamethasone (KRd) has been approved for the treatment of relapsed/refractory multiple myeloma (RRMM). We conducted a retrospective analysis of 197 RRMM patients (pts) between January 2016 and March 2018 in six Italian hematologic centers, with the aim to evaluate efficacy and safety of KRd in real‐life. At KRd initiation 27% carried high risk cytogenetic abnormalities (HRCA) [del17p and/or t(4;14) and/or t(14;16)], median number of prior lines of therapy was 2 (1–8), nearly all pts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
7
31
0
Order By: Relevance
“…Information on the prognostic impact of prior resistance to BTZ and/or LEN in KRD therapy is also limited in real-world observational studies, [11][12][13] while such information is mostly lacking for KD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the prognostic impact of prior resistance to BTZ and/or LEN in KRD therapy is also limited in real-world observational studies, [11][12][13] while such information is mostly lacking for KD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Median PFS was 19.8 months and 1 year OS was 80.6% with an ORR of 88%. Increased PFS and OS rates were observed in patients who received less than two prior line of therapies and overall, this study indicated KRd to be an effective regimen against relapsed or refractory MM outside of clinical studies without the emergence of novel safety concerns ( 109 ).…”
Section: Clinical Evaluations Of Carfilzomib In R/rmmmentioning
confidence: 77%
“…Rochchi et al. ( 109 ), investigated the efficacy and safety of carfilzomib, dexamethasone and lenalidomide therapy in relapsed or refractory MM patients in real world involving 197 patients. Most reported grade 3 or higher AEs included neutropenia (21%), infections (11%) and hypertension (6%).…”
Section: Clinical Evaluations Of Carfilzomib In R/rmmmentioning
confidence: 99%
“…12 Similarly, the addition of elotuzumab to Rd reduced the risk of progression by 30%, with a gain of 4.5 progression-free months compared with the control arm. 14 In this current study, in the lack of a randomized KRd vs. EloRd trial, and with the well-known limitations and susceptibility to the bias of real-life suggestions, 17 we weighed the relative usefulness of one triplet over the other, comparing a multicenter retrospective EloRd cohort 18 with four multicenter retrospective KRd cohorts, [19][20][21][22] all including RRMM cases treated outside of clinical trials. This current clinical practice study's overall results demonstrate that KRd therapy offers a superior outcome than EloRd.…”
Section: Significance Statementmentioning
confidence: 99%
“…After twelve cycles, K was reduced (days 1, 2, 15, and 16) and prolonged beyond 18 cycles at the physician's discretion. [19][20][21][22] In all five cohorts (EloRd and KRd), the dose of each drug was adjusted according to drug recommendations in case of specific preexisting comorbidities. In cases of specific predefined hematological and non-hematological toxic events, drugs' dosages were reduced, according to the manufacturers' recommendations and medical choice.…”
Section: Significance Statementmentioning
confidence: 99%